Analysis of the mathematical model of the gas bubbling curtain injection on the bottom and the walls of a continuous casting tundish. (14th September 2017) - Neves, L.; Tavares, R. P.
Abstract : In the present work, the behaviour of a gas bubbling curtain (GBC) in the continuous casting tundish of industry is studied by using a physical model in the scale of 1:3. This study was made with the following configurations of gas injection inside the tundish: no gas injection, gas injection on the bottom and combined gas injection (CGI) on the bottom and the walls. Mathematical simulations were performed using the Eulerian approach. Mathematical modelling was also used to determine the residence time distribution curves (RTD curves). For the validation of the mathematical model, experiments were made using the physical models to obtain the homogenisation time of salt solutions. All of the results were validated by the experimental results of the RTD curves. The plug flow fraction remained almost constant when gas injection was used on the walls, however the mean residence time and the dead volume fraction, increased and decreased, respectively. The CGI on the bottom and walls allowed the entire cross-section to be covered with the GBC which acted as a barrier to the passage of inclusions.